MAML2-Rearranged Mucoepidermoid Carcinoma of the Parotid Gland: A Report in a 20-Month-Old Toddler. (29th March 2022) - Owosho, Adepitan A.; Olatunji, Abiodun S.; Adejobi, Adewale F.; Fatusi, Olawumi A.; Okunade, Toluwaniyin; Maddux, Kelly; Shaw, Justin; Summersgill, Kurt F.
Abstract : Malignancies of salivary gland origin are rare in children. Mucoepidermoid carcinoma (MEC) is the most common histologic type of salivary gland neoplasm in pediatrics. We report a rare case of parotid MEC in a 20-month-old female patient. The tumor was composed of nests of epidermoid cells with nuclei appearing vesicular, pleomorphic, and hyperchromatic with an admixture of mucous cells and cystic spaces within a prominent connective tissue stroma. Immunohistochemically, the epidermoid cells showed cytokeratin 7 and P63 positivity, and mucous cells were positive for mucicarmine. Molecularly, this case was positive for MAML2 rearrangement by FISH. To our knowledge, this is one of the youngest cases of MEC of the parotid gland reported in the English literature.